From Gontor to Sorong: Muslim Minority Practices on Arabic Teaching and Learning - Wekke, Ismail Suardi; Andriansyah, Andriansyah (ASPENSI in Bandung, Indonesia, 2016)
ABSTRACT: âPesantrenâ, or Islamic boarding school, is a part of Islamic education institution growing in Indonesian culture and tradition. Arabic was chosen, because it is the premier language of Islamic religion and be started to expand Muslims capacity through training. This phenomenon is interesting to explore since âpesantrenâ entertain to charter foreign language as compulsory subject to master. This paper explores how âpesantrenâ conduct its Arabic learning and construct studentsâ skill in acquiring the language. This research was conducted in West Papua Province. All the regency and city were observed, excluded Wondama Regency, because the institutions there were not implemented Gontor Model as a source to teach Arabic. In-depth interview and non-participant observation were employed in collecting data. Research findings show that in implementing language learning, first step to do was curriculum enhancement and tried to adapt some model in delivering the subject. Teachers as the facilitator command the process of learning and tried the best effort to maintain practice in the school and âpesantrenâ neighborhood. The Foundation Management Board provided books and learning media to expand studentsâ language skills. The main media is environment, its existence strengthen communication exercise, and the same time to allocate studentsâ drill in understanding language context. Finally, the researchers recommend further research to other foreign languages. KEY WORD: Islamic Boarding School; Language Learning; Arabic; Foreign Language; Modernity.Â RESUME: âDari Gontor ke Sorong: Praktek Muslim Minoritas dalam Pengajaran dan Pembelajaran Bahasa Arabâ. Pesantren merupakan bagian dari institusi pendidikan yang tumbuh dalam tradisi dan budaya Indonesia. Bahasa Arab dipilih, karena merupakan bahasa utama agama Islam dan dimulai dari upaya untuk mengembangkan kapasitas Muslim melalui pendidikan. Fenomena ini menarik untuk dieksplorasi dimana pesantren menjadikan bahasa asing sebagai pelajaran yang harus dikuasai. Artikel ini mengkaji bagaimana pesantren menjalankan pembelajaran bahasa Arab dan mengkonstruksi keterampilan santri dalam menguasai bahasa yang diajarkan. Penelitian dilaksanakan di Provinsi Papua Barat. Semua kota dan kabupaten diamati, kecuali Kabupaten Wondama, karena lembaga pendidikan di sana tidak mengadopsi Model Gontor sebagai sistem pengajaran bahasa Arab. Wawancara mendalam dan pengamatan tak berpartisipasi digunakan dalam mengumpulkan data. Hasil penelitian menunjukan bahwa ada beberapa tahapan dalam penerapan pembelajaran bahasa, yang dimulai dari pengayaan kurikulum dan berupaya untuk mengadaptasi beberapa model yang sudah dilaksanakan dalam mengajarkan mata pelajaran. Guru merupakan fasilitator yang menjadi pemandu dalam pelaksanaan pembelajaran dan berusaha dengan cara terbaik untuk mempertahankan pelaksanaan praktek di sekolah dan lingkungan pesantren. Pengurus Yayasan menyediakan buku dan media pembelajaran untuk mendorong penguasaan keterampilan berbahasa santri. Media utama adalah lingkungan, keberadaannya memperkuat latihan berkomunikasi, dan pada saat yang sama menyediakan kesempatan bagi siswa untuk berlatih dalam memahami konteks berbahasa. Akhirnya, peneliti merekomendasikan penelitian lanjutan mengenai bahasa asing lainnya. KATA KUNCI: Pesantren; Pembelajaran Bahasa; Bahasa Arab; Bahasa Asing; Modernitas.Â Â About the Authors: Ismail Suardi Wekke earned his Doctoral degree from UKM (National University of Malaysia) with the kind supported by Ford Foundation International Fellowship Program. He is a Junior Lecturer at the STAIN (State Islamic College) Sorong, Jalan Klamono-Sorong Km.17, Klablim, Sorong 98417, West Papua, Indonesia. Andriansyah is doing his research on history. He is Graduate Student at the UGM (Gadjah Mada University), Jalan Bulaksumur, Yogyakarta 55281, Indonesia. Corresponding author is: iswekke@gmail.comHow to cite this article? Wekke, Ismail Suardi & Andriansyah. (2016). âFrom Gontor to Sorong: Muslim Minority Practices on Arabic Teaching and Learningâ in SOSIOHUMANIKA: Jurnal Pendidikan Sains Sosial dan Kemanusiaan, Vol.9(1) May, pp.49-54. Bandung, Indonesia: Minda Masagi Press and UPI Bandung, ISSN 1979-0112. Chronicle of the article: Accepted (January 28, 2016); Revised (April 15, 2016); and Published (May 30, 2016).